The influence of academic staff job performance on job burnout: the moderating effect of psychological counselling - Lei, Miao; Alam, Gazi Mahabubul; Bashir, Karima (Springer Nature, 2025)
Current research on addressing burnout in higher education predominantly focuses on post-measurements, after job burnout has occurred, rather than emphasizing the long-recognized tradition of preventive philosophy and applying pre-measurements of burnout. This study focuses on the influence of academic staff job performance on job burnout, as well as the moderating effect of psychological counselling. Using a quantitative approach with panel data over a four-year period, information was collected from 1091 academic staff across 12 universities. It utilized archived data on their job performance (KPI) and mental health reports. The findings revealed that job performance exerts a negative influence on burnout (β = −0.037, P < 0.001). Furthermore, psychological counselling moderates the relationship between job performance and job burnout (β = −0.005, P < 0.001), although it does not directly enhance job performance. Overall, this research contributes to understanding and addressing burnout among academic staff, by suggesting that job performance and psychological counselling can serve as preventive measures against burnout. Therefore, universities are encouraged to implement proactive recruitment strategies that assess academic staff holistically so that the onset of burnout can be mitigated.